2014
DOI: 10.1371/journal.pone.0090684
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Expectation-Violating Concepts: The Effects of Agents and Cultural Familiarity

Abstract: Previous research has shown that ideas which violate our expectations, such as schema-inconsistent concepts, enjoy privileged status in terms of memorability. In our study, memory for concepts that violate cultural (cultural schema-level) expectations (e.g., “illiterate teacher”, “wooden bottle”, or “thorny grass”) versus domain-level (ontological) expectations (e.g., “speaking cat”, “jumping maple”, or “melting teacher”) was examined. Concepts that violate cultural expectations, or counter-schematic, were rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…However, it is still unknown what effects of expectancy incongruence would be at later time points in encoding‐related LPP. In terms of stimulus retrieval, according to the abovementioned distinctiveness theory and related empirical studies (e.g., Chang & Sanfey, ; Kroneisen & Bell, ; Lin, Xiang, et al, ; Porubanova et al, ; Schmidt, ), we predict that, in the present study, expectancy incongruence might alter the distinctiveness of the pictures, particularly that of neutral pictures, during the encoding phase and thus would enhance recognition performance (e.g., the sensitivity index d′ ) and increase P2 amplitude but decrease recognition‐related LPP amplitude for neutral pictures. In contrast to neutral pictures, however, negative pictures are distinctive regardless of expectancy incongruence.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…However, it is still unknown what effects of expectancy incongruence would be at later time points in encoding‐related LPP. In terms of stimulus retrieval, according to the abovementioned distinctiveness theory and related empirical studies (e.g., Chang & Sanfey, ; Kroneisen & Bell, ; Lin, Xiang, et al, ; Porubanova et al, ; Schmidt, ), we predict that, in the present study, expectancy incongruence might alter the distinctiveness of the pictures, particularly that of neutral pictures, during the encoding phase and thus would enhance recognition performance (e.g., the sensitivity index d′ ) and increase P2 amplitude but decrease recognition‐related LPP amplitude for neutral pictures. In contrast to neutral pictures, however, negative pictures are distinctive regardless of expectancy incongruence.…”
Section: Introductionmentioning
confidence: 53%
“…For instance, the distinctiveness theory indicates that distinctiveness enhances stimulus retrieval, and expectancy incongruence is a phenomenon of distinctiveness (Schmidt, ). Consistently, in a behavioral study by Porubanova and colleagues (), participants were asked to memorize presentations of everyday concepts that were incongruent or congruent with expectations (e.g., a stone mirror and a convertible car, respectively) and were subsequently prompted to recall all of these concepts. The results showed that expectancy incongruent concepts were more memorable than congruent concepts.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…As has been suggested by Boyer (2001) and Porubanova and her colleagues (Porubanova-Norquist, Shaw and Xygalatas, 2013;Porubanova-Norquist et al, 2014), agents who violate either intuitive ontology or expectations induced through cultural conditioning become particularly memorable as figures inspiring religious cults and gaining the attention of supplicants. However, the mythical sagas and the healing narratives concerning Asclepius focus less on his figure as a divine agent than on his activity and achievements.…”
Section: Resultsmentioning
confidence: 94%
“…Este tipo de sesgos arraigarían la adherencia a creencias dentro de un contexto social determinado, donde la familia, la comunidad y el aprendizaje cultural juegan un papel fundamental en el compromiso del individuo con un sistema de creencias. Por último, pero no menos importante, Porubanova, Shaw, McKay & Xygalatas (2014) demuestran experimentalmente como las ideas que producen una violación de expectativas culturales parecen ser más fáciles de recordar que las relacionadas con principios ontológicos naturales, cuestión que trae consigo muchas relecturas acerca de la importancia de la contraintuitividad en la propagación de las ideas religiosas.…”
Section: Creencias Agentes Sobrenaturales Y Contraintuitividadunclassified